DETAILED STUDY OF USER’S INTENTION AND CONSCIOUSNESS OF SERVICE QUALITY IN KARPAGAM UNIVERSITY CENTRAL LIBRARY - KRISHNASWAMY, Dr. N. (IJRDO - Journal of Social Science and Humanities Research, 2016)
The study aimed at investigating the user’s Intention and Consciousness of services quality provided by the Central Library of Karpagam University. Survey among library users was administered and data was collected with the help of questionnaire. Findings of the study revealed that the Central Library of Karpagam University is offering good quality of services for its users. Respondents were satisfied with different library services including, library books, journals, dictionaries, encyclopedias, Internet services, special collection, periodical collections, reference service, reading room facility, library environment, opening hours and attitude of library staff with the library users. Respondents demanded e-resources of information in the library and suggested that library should provide training programs for its users to make the better use of library services. Study concludes that the overall services quality offered by the Central Library of Karpagam University is satisfactory. A total of 825 questionnaires were received indicating 84.6% overall response rate.gap analysis was used to determine the service quality gap between desired service intention and actual service consciousness. The most important area expected by users was relevance of information received followed by access to journals and adequate lighting in reading areas.